Implementing integrated-youth services virtually in British Columbia during the COVID-19 pandemic. Issue 1 (19th August 2022) - Zenone, Marco; Raimundo, Al; Nanji, Suhail; Uday, Neha; Tee, Karen; Ewert, Alayna; Helfrich, Warren; Chan, Godwin; Mathias, Steve; Barbic, Skye
Abstract : Objective: During the COVID-19 pandemic, Foundry responded to support youth across the province of British Columbia (BC), Canada, by creating a virtual platform to deliver integrated services to youth. In this paper, we report on the development of Foundry Virtual services, initial evaluation results and lessons learnt for others implementing virtual services. Methods and analysis: In April 2020, Foundry launched its virtual services, providing young people and their caregivers from across BC with drop-in counselling services via chat, voice or video calls. Foundry consulted with youth and caregivers to implement, improve and add services. Using Foundry's quality improvement data tool, we document service utilisation, the demographic profile of young people accessing virtual services, and how young people rate the quality of services accessed. Findings: Since launching, 3846 unique youth accessed Foundry Virtual services over 8899 visits, totalling 11 943 services accessed. The predominant services accessed were walk in counselling (32.5%), mental health and substance use services (31.4%), youth peer support (17.2%) and group services (7.3%). Over 95% of youth reported that they would recommend virtual services to a friend. Conclusion: In response to our early findings, we provide three recommendations for other implementers. First, engage the audience in which you intend to serve at every phase of the project. Second, invest in the needs of staff to ensure they are prepared and supported to deliver services. Last, imbed a learning health system to allow for the resources culture of continuous learning improvement that allows for rapid course adjustments and shared learning opportunities.